2019
DOI: 10.1080/1828051x.2019.1698325
|View full text |Cite
|
Sign up to set email alerts
|

Performance, antioxidant status, nutrient retention and serum profile responses of laying Japanese quails to increasing addition levels of dietary guanidinoacetic acid

Abstract: (2020) Performance, antioxidant status, nutrient retention and serum profile responses of laying Japanese quails to increasing addition levels of dietary guanidinoacetic acid,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 48 publications
1
11
0
Order By: Relevance
“…The plasma creatinine level was elevated by the dietary inclusion of 1.8 g/kg GAA. Similar results were observed when broilers [76] and Japanese quails [47] were fed diets supplemented with GAA. Creatinine is the end-product of skeletal muscle creatine and phosphocreatine degradation and diffuses from the muscle into the bloodstream before being excreted by the kidneys [77].…”
Section: Discussionsupporting
confidence: 81%
See 3 more Smart Citations
“…The plasma creatinine level was elevated by the dietary inclusion of 1.8 g/kg GAA. Similar results were observed when broilers [76] and Japanese quails [47] were fed diets supplemented with GAA. Creatinine is the end-product of skeletal muscle creatine and phosphocreatine degradation and diffuses from the muscle into the bloodstream before being excreted by the kidneys [77].…”
Section: Discussionsupporting
confidence: 81%
“…Ahmadipour et al [46], and Raei et al [47], increased NO concentrations were reported following GAA supplementation. According to an orthogonal contrast analysis, feeding experimental diets containing ARG and GAA with or without PHE also decreased RV to TV ratio, relative heart weight, and ascites mortality, possibly due to the higher plasma NO levels of birds fed these diets.…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…Adding GAA to the diet does not seem to be an effective technique for boosting laying hen performance (Khakran et al, 2018). When laying quails were fed varied doses of dietary GAA supplementation (0, 0.6, 1.2, and 1.8 g/kg), the greatest laying rate was attained with 1.8 g/kg of GAA, while the optimum egg weight, egg mass, shell, and yolk weight was recorded with 1.2 g/kg of GAA (Raei et al, 2020). When laying hens were fed a reduced protein diet with supplemental GAA, egg production and feed intake decreased compared to the control diet (Dao et al, 2021).…”
Section: Gaa Supplementation and Reproductionmentioning
confidence: 99%